EJMM 2020
DOI: 10.51429/ejmm29404
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Infectious Causes of Diarrhea and Genetic Determination of Diarrheagenic E. coli using Multiplex PCR in under 5 Years Children in Egypt

Abstract: Background: Infectious diarrhea represents a life-threatening problem among children in developing countries. Objectives: This work aimed to study bacterial, viral and parasitic causes of acute diarrhea; with genetic determination of diarrheagenic E. coli (DEC) in <5 years children. Methodology: Stool specimens were collected from 206 diarrheal children. Bacterial agents were isolated and identified by standard microbiological procedures. Multiplex PCR was done for genetic determination of DEC subtypes. ELI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
1
2
0
1
Order By: Relevance
“…Many studies indicated that the presence of phenyl ring an methyl attached to the sulfonamide moiety increased the antimicrobial potential of the synthesized compounds against the tested microbial strains; these results are coherent with our results [26,28] . Moreover, due to their utilization in numerous commercial medicine designs, particularly those containing nitrogen atoms, heterocyclics are recognized as an essential family of drugs [29] …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Many studies indicated that the presence of phenyl ring an methyl attached to the sulfonamide moiety increased the antimicrobial potential of the synthesized compounds against the tested microbial strains; these results are coherent with our results [26,28] . Moreover, due to their utilization in numerous commercial medicine designs, particularly those containing nitrogen atoms, heterocyclics are recognized as an essential family of drugs [29] …”
Section: Discussionsupporting
confidence: 91%
“…[26,28] Moreover, due to their utilization in numerous commercial medicine designs, particularly those containing nitrogen atoms, heterocyclics are recognized as an essential family of drugs. [29] Bouzina and al. [30] evaluated the antibacterial activity of a new series of sulfamidocarbonyloxyphosphonates and demonstrated that all tested compounds had an important inhibition against Gram negative strains than Gram positive.…”
Section: Discussionmentioning
confidence: 99%
“…Selain itu, aplikasi akuntansi seluler menyederhanakan penggunaan alat akuntansi, memungkinkan UMKM untuk menghitung biaya dan menentukan harga dengan lebih mudah (Susilowati & Sigit, 2020). Selain itu, pendekatan gamifikasi dalam aplikasi pencatatan keuangan berbasis seluler meningkatkan motivasi dan keterlibatan pengguna, membantu individu mengenali kondisi keuangan pribadi mereka dengan lebih baik (Hassan et al, 2013). Secara keseluruhan, aplikasi mobile untuk pencatatan keuangan menawarkan UMKM keuntungan dari efektivitas, efisiensi, akurasi, dan motivasi dalam mengelola keuangan mereka dan membuat keputusan yang tepat.…”
Section: A Latar Belakangunclassified
“…In organic chemistry, it helps understanding concepts, for example, regarding the molecular structure and explaining reaction pathways and chemical mechanisms through the estimation of compounds' geometrical properties [8] . It may also deliver fine details of the electronic properties of reactants, intermediates, and products as well as support and explain various experimental observations [9,10]. The still growing interlocking of experimental and computational chemistry has solved a wide range of organic chemical problems.…”
Section: Introductionmentioning
confidence: 99%